ChatGPT as an Academic Support Tool on the Academic Performance among Students: The Mediating Role of Learning Motivation - Kevin D. Caratiquit; Lovely Jean C. Caratiquit (Journal of Social, Humanity, and Education, 2023)
Purpose: This study aimed to investigate the mediating role of learning motivation in the association between ChatGPT, which was employed as an academic support tool, and students' academic performance. Methodology: This study employed a mixed-method triangulation research design to investigate the correlation between the use of ChatGPT for academic support, learning motivation, and student performance. The study utilized a mediation analysis employing  Preacher and Hayes approach. The study comprised a sample of 178 learners enrolled in a secondary educational institution in Lal-lo, Cagayan, the Philippines, and was selected using purposive sampling. Results: The research findings demonstrated that the influence of ChatGPT as an educational aid on students' academic performance is fully mediated by their learning motivation. The utilization of the ChatGPT has been observed to have a positive impact on academic performance by enhancing learning motivation. Effective and ethical employment of ChatGPT plays a significant role in promoting educational progress and enhancing academic achievement among students, thereby fostering their motivation to acquire knowledge. Conclusions: Learning motivation fully mediates the effect of ChatGPT on students’ academic performance. ChatGPT enhances students’ interest, curiosity, and intrinsic motivation, leading to greater engagement and improved academic outcomes. Limitations: This study did not incorporate additional variables that may impact the association between ChatGPT as an academic support tool, learning motivation, and students’ academic performance. Contributions: Understanding the mediating role of learning motivation can offer valuable insights for educational professionals and policymakers to develop effective interventions that utilize AI-based tools to strengthen students' motivation and, as a result, improve their academic performance.